Prevalence of self-reported hypertension and its relation to dietary habits, in adults; a nutrition & health survey in Greece - Xenaki Dimitra; Panagiotakos Demosthenes B; Milias George A; Pitsavos Christos; Panagopoulos George; Stefanadis Christodoulos (BMC, 2006)
Abstract Background Hypertension leads to many degenerative diseases, the most common being cardiovascular in origin. This study has been designed to estimate the prevalence of self-reported hypertension in a random nationwide sample of adult Greek population, while focus was set to the assessment of participants' nutritional habits in relation to their hypertension status. Methods A random-digit dialed telephone survey. Based on a multistage, stratified sampling, 5003 adults (18 - 74 yr) participated (men: 48.8%, women: 51.2%). All participants were interviewed via telephone by trained personnel who used a standard questionnaire. The questionnaire included demographic and socioeconomic characteristics, medical history, lifestyle habits and nutritional assessment. Results The prevalence of self-reported hypertension was 13.3% in men and 17.7% in women (P < 0.001). Furthermore, women reported higher values of systolic blood pressure (180 ± 27 mmHg) than men (169 ± 24 mmHg). Positive relationships were found between hypertension status and the prevalence of the rest investigated health conditions (i.e. hypercholesterolaemia, diabetes mellitus, renal failure and obesity). Nutritional assessment showed that consumption of fish, fruits and juices, cereals, and low fat milk and yogurt was significantly higher among hypertensive subjects while the opposite was observed for food items as red meat, pork, egg, pasta and rice, full fat dairy products and desserts. Conclusion Hypertension seems to be a serious public health problem in Greece. It is encouraging that hypertensives may have started adopting some more healthy nutritional behaviour compared to normotensive ones. However, they can gain significant benefits regarding to blood pressure control, if they increase the level of compliance with dietary recommendations.